Targeted Drug Delivery — From Magic Bullet to Nanomedicine: Principles, Challenges, and Future Perspectives - Tewabe, Ashagrachew; Abate, Atlaw; Tamrie, Manaye; Seyfu, Abyou; Abdela Siraj, Ebrahim (Journal of multidisciplinary healthcare, 2021)
Nanomedicine is an advanced version of Paul Ehrlich's "magic bullet" concept. Targeted drug delivery is a system of specifying the drug moiety directly into its targeted body area (organ, cellular, and subcellular level of specific tissue) to overcome the aspecific toxic effect of conventional drug delivery, thereby reducing the amount of drug required for therapeutic efficacy. To achieve this objective, the magic bullet concept was developed and pushed scientists to investigate for more than a century, leading to the envisioning of different nanometer-sized devices - today's nanomedicine. Different carrier systems are being used and investigated, which include colloidal (vesicular and multiparticulate) carriers, polymers, and cellular/subcellular systems. This review addresses the need for and advantages of targeting, with its basic principles, strategies, and carrier systems. Recent advances, challenges, and future perspectives are also highlighted.